Perceptions about the political–scientific community and its role in formulating the problems of public policy for science, technology and innovation in Costa Rica - Viales Hurtado, Ronny José (2012)
A Special Commission was created in 2006 under the auspices of the Agricultural Affairs Commission, to discuss possible reforms to the June 1990 Public Law No. 7169, relating to the promotion and development of science and technology (S&T) in Costa Rica. For this purpose, various strategic actors in the country were summoned to provide information about the diverse activities that were being carried out regarding this topic, and to discuss their perspectives on the current state of science, technology and innovation in Costa Rica. This paper uses a network approach to examine the main actors and their relationships in order to systematize their views and perspectives on S&T and their relative influence on public policies for S&T in Costa Rica